Implementasi Data Mining dalam Menentukan Jarak Pengiriman yang Minimum pada Produk Minyak Goreng Menggunakan Metode K-Means Clustering dan Simulated Annealing di CV. Bima Laras Khatulistiwa - Cahyono, Jordyan Akmal; Sumiati, Sumiati (Universitas Batanghari Jambi, 2025)
This study aims to determine the number of customer clusters and the optimal total delivery distance in the distribution of cooking oil products at CV. Bima Laras Khatulistiwa using the concept of data mining with the K-Means Clustering and Simulated Annealing methods. The results of this study concluded that the number of customer clusters consists of 3 (three) clusters, namely cluster 0 with 58 data, cluster 1 with 10 data, and cluster 2 with 59 data and the total distance traveled in the distribution of Minyak Kita products is 278.57 km, with details of the distance traveled for cluster 0 of 132.74 km, cluster 1 of 28.3 km, and cluster 2 of 117.53 km.